Electron states and related optical responses in asymmetric inverse parabolic quantum wells (2013)
ABSTRACT: The article reports the obtention of the conduction band energy states for electrons in a AlxGa1x As-based quantum well with inverse parabolic confinement. Accordingly, it has been possible to calculate the intersubband electron-transition-related optical absorption and rectification coefficients. The comparison between the results in the cases of symmetric and asymmetric rectangular barrier configurations allows to verify the possibility of the second-order optical rectification in the asymmetric case as well as a rather drastic change in the absorption coefficient as a function of the height of the inverse parabolic potential in such a configuration. Keywords: Quantum well, Nonlinear optics, Modulation doping, Electronic states.